Problems in patient management and the impact of osteoporosis therapy on the incidence of clinical infection - O. M. Lesnyak; E. N. Gladkova; K. E. Zotkina; A. L. Grigoryeva; Yu. A. Safonova; O. Yu. Kuznetsova; M. A. Pokhaznikova (Научно-практическая ревматология)
The global diversion of health resources during the COVID-19 pandemic from the provision of routine medical care, and the more frequent and severe course of this infection in older patients justify the need to study the impact of the pandemic on the management of patients with osteoporosis.Aim – to assess the impact of the COVID-19 pandemic on the management of patients with osteoporosis, as well as the impact of anti-osteoporotic drugs on the incidence of COVID-19.Material and methods. A cross-sectional study was conducted, including a telephone survey and analysis of outpatient records of 304 patients with osteoporosis, who were recommended therapy with anti-osteoporotic medications. The average age was 70.8±8.8 years. The vast majority of patients took bisphosphonates in oral or parenteral forms.Results. Problems with the timely conduct of laboratory tests were noted by 91 (30.4%) subjects, DXA testing – 98 (32.8%). 65 (22.1%) were unable to receive the drug in a timely manner. Problems were more common when taking parenteral drugs (p=0.002). The cumulative incidence of COVID-19 was 12.2%, which is twice as high as in the population. There was a tendency to a lower incidence of confirmed SARS-CoV-2 infection when treated with denosumab or zoledronic acid. COVID-19 cases were not associated with either a vitamin D dose or a 25(OH)D level.Conclusions. During the COVID-19 pandemic, there is a significant decline in the quality of medical care for patients with osteoporosis, which cannot but lead to a new epidemic in the future – an epidemic of low-energy fractures. Our data confirmed the predisposition of older age groups to a higher incidence of COVID-19. However, there is no clear association of osteoporosis therapy with the risk of developing clinical manifestations of COVID-19.